THE EFFECT OF TAX AVOIDANCE ON COST OF DEBT WITH GROWTH OPPORTUNITY AS A MODERATING VARIABLE - Pramiana, Omi; Sari, Corrina Dian Anita (Universitas Islam Kadiri, 2025)
This study's goal is to examine how tax evasion affects borrowing costs and development opportunities as a moderating factor in the Indonesia Stock Exchange-listed energy industry. The financial statements of businesses listed on the Indonesia Stock Exchange serve as the second-order data used in this study. Purposive sampling was used in the sampling process in order to collect samples that satisfied the requirements. The energy industry that was listed on the Indonesia Stock Exchange between 2019 and 2021 serves as the study's example. Over the course of three years, 52 firms in all were employed as study samples, resulting in 156 samples. In this study, regression analysis and moderated regression analysis were employed. The cost of debt is positively impacted by tax evasion, according to the data analysis findings. Creditors must raise borrowing charges because they consider tax evasion to be a dangerous activity. Opportunities for growth cannot lessen the effect of tax evasion on debt costs.